Evaluasi Status Kesuburan Tanah Berbasis Sistem Informasi Geografis (SIG) pada Lahan Subak di Kecamatan Denpasar Barat, Kota Denpasar, Provinsi Bali - RACHMADYA, BAYU; TRIGUNASIH, NI MADE; SUPADMA, A.A. NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Evaluation of Soil Fertility Status with Geographic Information System (GIS) Based on Subak Land at West Denpasar District, Denpasar City, Bali Province This study aims to determine the status of soil fertility, to determine the characteristics of the soil which is a limiting factor to the status of soil fertility, to provide recommendations for land management, and to determine the spatial distribution of soil fertility status on Subak land in West Denpasar District. This research was conducted from December 2020 – March 2021. The method used in this research is the field survey method and soil test with fertility status parameters including Cation Exchange Capacity, Base Saturation, C-Organic, Total phosphate, and Total potassium with reference to the Technical Guidelines for Evaluation of Soil Fertility Bogor Soil Research Center (1995). The results showed that the soil fertility status at the study site was classified as moderate (Subak Pagutan) and high (Subak Semila; Subak Mergaya; Subak Tegal Buah; Subak Tegallantang). Parameters of low total P content in Pagutan Subak and moderate in Semila Subak, Tegal Buah Subak, and Tegallantang Subak as well as moderate K-total content in all subaks are the limiting factors in this fertility status so it is necessary to apply phosphate fertilization in Subak which has a limiting P-total and potassium fertilization as well as adding organic matter to the entire Subak.